2007
DOI: 10.1007/s11120-007-9192-y
|View full text |Cite
|
Sign up to set email alerts
|

A Brownian dynamics computational study of the interaction of spinach plastocyanin with turnip cytochrome f: the importance of plastocyanin conformational changes

Abstract: Brownian Dynamics (BD) computer simulations were used to study electrostatic interactions between turnip cytochrome f (cyt f) and spinach plastocyanin (PC). Three different spinach PC structures were studied: The X-ray crystal structure of Xue and coworkers [(1998) Protein Sci 7:2099-2105] and the NMR structure of Musiani et al. [(2005) J Biol Chem 280:18833-18841] and Ubbink and co-workers [(1998) Structure 6:323-335]. Significant differences exist in the backbone conformation between the PC taken from Ubbink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…BD analyses are quite sensitive to small changes in conformation of the proteins that are being modeled. For instance, the C f –Pc complex with spinach Pc adopted two different conformations when using distinct structural data sources [50]. On the basis of such finding, it was suggested that Pc may assume distinct conformations in solution so as to yield a productive ET complex.…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…BD analyses are quite sensitive to small changes in conformation of the proteins that are being modeled. For instance, the C f –Pc complex with spinach Pc adopted two different conformations when using distinct structural data sources [50]. On the basis of such finding, it was suggested that Pc may assume distinct conformations in solution so as to yield a productive ET complex.…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…The resulting kinetic data have been very useful to analyse the interaction between Pc and Cf by means of theoretical methods, including Molecular Dynamics (MD) at sub-nanosecond time scale [17], rigid-body MD [18], Molecular Modelling [19] supported by NMR data and Brownian Dynamics (BD) simulations [20][21][22][23][24][25][26][27][28]. Last computations, in particular, are in good agreement with experimentally calculated reaction rates [21,[24][25][26], thereby explaining many effects of ionic strength and mutations on the kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that different conformations of Pc lead to different BD data [22] and that the geometry of the copper centre of Pc is perturbed upon binding to Cf [32]. In addition, the role of the small domain of Cf in Pc docking is not fully understood, and there still exist some discrepancies to reconcile structural and functional data, especially in Phormidium cyanobacterium.…”
Section: Introductionmentioning
confidence: 99%
“…However, these proteins seem to be in head‐on orientation. Later Gross and co‐authors used BD simulations of Cyt f and Pc complex formation in higher plants (Gross ), green algae Chlamydomonas reinhardtii (Haddadian and Gross , b), cyanobacterium P. laminosum (Gross ) and Cyt f from P. laminosum with various cyanobacterial plastocyanins (Gross and Rosenberg ).…”
Section: Introductionmentioning
confidence: 99%